MODEL PEMBELAJARAN TERINTEGRASI di SMA TERPADU DARUSSALAM RAJAPOLAH TASIKMALAYA JAWA BARAT - Muhammad Hasan Basari (JURNAL ILMIAH EDUKATIF, 2021)
Integrated learning is a learning strategy to make it more meaningful for life. In Islamic education, it is formed and based on the values ​​of faith and piety that are nurtured continuously so that attitudes, knowledge and skills are developed. Integrated learning or integrated learning is applied in pesantren-based schools, providing knowledge by combining religious and general curricula. The reality is that there are still many who only combine the general curriculum and the pesantren curriculum, so an effort is needed through techniques, methods and learning models. The purpose of this study was to identify an integrated learning model in this school. The method uses a descriptive type case study with a qualitative approach and observation, interview and documentation techniques. The results of this study indicate that integrated learning is carried out with a stand-alone subject model that is integrated with the curriculum of salafi pesantren, KMI Gontor and boarding schools for 24 hours. The conclusion is that integrated learning at SMA Terpadu Darusalam Tasikmalaya has been implemented by integrating the integrated curriculum by incorporating the concepts of Islamic boarding school in the pesantren culture.